2014
DOI: 10.1186/1472-6963-14-172
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s perception of sexual and reproductive health services in Kenya

Abstract: BackgroundAddressing the Sexual and Reproductive Health (SRH) needs of young people remains a big challenge. This study explored experiences and perceptions of young people in Kenya aged 10–24 with regard to their SRH needs and whether these are met by the available healthcare services.Methods18 focus group discussions and 39 in-depth interviews were conducted at health care facilities and youth centres across selected urban and rural settings in Kenya. All interviews were tape recorded and transcribed. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(148 citation statements)
references
References 20 publications
(23 reference statements)
7
133
0
Order By: Relevance
“…Other studies conducted across sub-Saharan Africa corroborate with the WHO study with respect to barriers to adolescent HTC (18,20,(22)(23)(24)(26)(27)(28)(29)(30)(31)(32). These studies identified major barriers as fear of a positive test, especially among those sexually active, and fear of stigma and discrimination, including being ostracized by friends and family.…”
Section: Willingness To Test and Barrierssupporting
confidence: 65%
“…Other studies conducted across sub-Saharan Africa corroborate with the WHO study with respect to barriers to adolescent HTC (18,20,(22)(23)(24)(26)(27)(28)(29)(30)(31)(32). These studies identified major barriers as fear of a positive test, especially among those sexually active, and fear of stigma and discrimination, including being ostracized by friends and family.…”
Section: Willingness To Test and Barrierssupporting
confidence: 65%
“…Given that only 27% of the respondents knew of any adolescent/youth friendly services shows that knowledge remains a problem in the effort to address the unique sexual and reproductive health needs of the target population as also noted by [17] and [23]. Failure to recognize one of the few existing services which has been operating for up to 14 years also confirms very low awareness by the agency and hosting institution and a need to refocus on this unit.…”
Section: Discussionmentioning
confidence: 83%
“…Not knowing where to go for services or a lack of understanding about the services provided were identified as barriers to seeking SRH or STI care [20, 21, 29, 30]. In some studies, youth reported that they were afraid to seek services because they didn’t understand what would happen during a clinic visit [22, 30].…”
Section: Resultsmentioning
confidence: 99%